Cassava Starch as an Effective Texture Corrector of Fat-Free Dairy Products Based on Symbiotic Starter Culture - Maxim S. Tsyganov; Galina O. Ezhkova; Maya A. Kharitonova; Elena V. Nikitina (International Journal of Food Science)
Cassava starch can be an effective texture corrector for dairy products; however, the presence of a starchy taste in such products is undesirable. A possible solution to this problem can be the use of partially hydrolyzed cassava starch; complex microbial amylase preparations, for instance, Amylosubtilin® or Bacillus licheniformis amylases, can be used as an enzyme. The use of these enzyme preparations in low concentration allows it to obtain cassava starches with increased solubility, which can be easily used in the technology of dairy products. Starch is partially hydrolyzed by amylase preparations and does not significantly affect the chemical composition of the protein part of the Symbilact dairy product. Positive dynamics of the rheological and antioxidant properties of the low-fat dairy product “Symbilact” from the enzyme-modified cassava starch during storage were revealed in the researches. AT starches are more able to correct the structure, especially AT-0.5 and AT-1, but to a less extent increase antioxidant properties. As matter of a fact, BT starches exhibit higher antioxidant potential, but less structure correction.